2017
DOI: 10.7759/cureus.1038
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D Deficiency Lead to Hypertension?

Abstract: Hypertension (HTN) or high blood pressure is one of the most chronic and deadliest disorders in the world. There are many risk factors responsible for HTN which include age, race, using tobacco, high salt intake, etc. One of the risk factors we would like to highlight is low vitamin D levels. While there is strong evidence that Vitamin D plays an important role in maintaining bone and muscle health, there has been recent debate regarding its role in hypertension. However, there are many studies that have shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
(37 reference statements)
0
30
1
7
Order By: Relevance
“…One of the reasons behind the findings of the current study and the above-mentioned studies could be due to the big difference in the sample size (the current study had a smaller sample size). Although the current study did not find any association between vitamin D (25(OH)D) and blood pressure, it has been reported that low vitamin D status is associated with an elevated prevalence of hypertension [ 34 ]. Furthermore, it was revealed that significantly increased rates of hyperlipidaemia, diabetes and peripheral vascular diseases were observed in people with low levels of 25(OH)D [ 35 ].…”
Section: Discussioncontrasting
confidence: 82%
“…One of the reasons behind the findings of the current study and the above-mentioned studies could be due to the big difference in the sample size (the current study had a smaller sample size). Although the current study did not find any association between vitamin D (25(OH)D) and blood pressure, it has been reported that low vitamin D status is associated with an elevated prevalence of hypertension [ 34 ]. Furthermore, it was revealed that significantly increased rates of hyperlipidaemia, diabetes and peripheral vascular diseases were observed in people with low levels of 25(OH)D [ 35 ].…”
Section: Discussioncontrasting
confidence: 82%
“…Our study revealed that a lower serum level of vitamin D3 was associated with ischemic stroke at 1.02 odds ratio. The potential mechanism for the association between vitamin D levels and ischemic stroke is likely to be linked with the association between low levels of 25-OH-vitD and traditional risk factors of ischemic stroke such as hypertension, thrombosis, and atherosclerosis [16,[32][33][34]. Vitamin D3 has an important neuroprotective role through several mechanisms such as induction of the endogen pathway of antioxidant system and suppression of inflammatory cytokines [15].…”
Section: Controlmentioning
confidence: 99%
“…Among adults, a wealth of observational data has demonstrated a relationship between low serum levels of 25OHD and hypertension [12][13][14], although no evidence of a clinically significant reduction in BP as a result of vitamin D supplementation has been observed [14].…”
Section: Introductionmentioning
confidence: 99%